Requirement of clathrin heavy chain for p53-mediated transcription - Enari, Masato (Cold Spring Harbor Laboratory Press, 2006)
The p53 protein is a transcription factor that activates various genes responsible for growth arrest and/or apoptosis in response to DNA damage. Here, we report that clathrin heavy chain (CHC) binds to p53 and contributes to p53-mediated transcription. CHC is known to be a cytosolic protein that functions as a vesicle transporter. We found, however, that CHC exists not only in cytosol but also in nuclei. CHC expression enhances p53-dependent transactivation, whereas the reduction of CHC expression by RNA interference (RNAi) attenuates its transcriptional activity. Moreover, CHC binds to the p53-responsive promoter in vivo and stabilizes p53–p300 interaction to promote p53-mediated transctiption. Thus, nuclear CHC is required for the transactivation of p53 target genes and plays a distinct role from clathrin-mediated endocytosis.